(untitled) (Bangladesh Journal of Microbiology, 2019)
A common member of the intestinal microbiota in humans and animals is Escherichia coli. Based on the presence of virulence factors, E. coli can be potentially pathogenic. The focus of this study was to determine genotypic diversity among clinical strains of E. coli. Test isolates were identified by biochemical, culture-based and molecular tests. Partial sequence of 16s rDNA was determined by Polymerase Chain Reaction using universal primers. The sequences were used as input in Basic Local Alignment Search Tool (BLAST) to reconfirm the identity of the isolates. Sequences were edited in Chromas and aligned in Bioedit. Afterwards, sequences were fed into Mega 5 and a dendogram was constructed. We used three sequences deposited in GenBank for comparison with our test sequences. It was found that two of our sequences showed similarity to the reference sequences. One of the isolates was similar to a Uropathogenic and a commensal E. coli. The other isolate showed similarity to a UPEC strain. It is possible that both of these isolates were commensal bacteria that led to opportunistic infection in the patients. The rest of the nine strains were different from the reference sequences. These isolates may be opportunistic pathogens that have undergone mutation events leading to sufficiently different rDNA sequences from the reference bacteria. Or they may also be pathogenic strains that caused infection in patients. This study indicated that clinical isolates of E. coli show variation in terms of their rDNA sequences. In order to study their phylogeny, other supporting tools such as investigation for phylogenetic markers, RAPD, ARDRA, ERIC-PCR, ribotyping, etc. may be used to study variation among isolates to a more significant extent. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 97-101